“Metodología para la planificación de la construcción de obras de regeneración urbana”. - Cabrera Morales, Walter Octavio (2017)
The principal problem that analyzed in the present work of investigation is, how there is planned the construction of works of urban regeneration? The central aimwas, TO ANALYZE the methodologies that exist for the planning by means of the bibliographical investigationfor the construction of works of urban regeneration. The investigation I use the methods theoretically, inductive and deductive it was realized by an approach more qualitative than quantitative, looking for the reasons and facts that are investigated. The basic modality was to look for the existing bibliography both in books and in scientific articles; of field checking and analyzing project documents of urban regeneration of avenues constructed like also observing and crossing the current conditionof the regenerated avenues. The type of investigation will be exploratory for that tries TO DESIGN a methodology for the planning of the construction of urban works of regeneration. Since result obtained a Methodology for the Planning of the construction of works of urban regenerations, which will be able to be applied in the sector of the construction and it is constituted by 21 processes in 9 areas of knowledge of The guide of the PMBOK. One presents the philosophies of Read Construcction, Last Planner to improve the planning (Managing of resources - programmings) and in the moment of control.